Substituted 4-Acyl-5-methyl-2-phenyl-pyrazol-3-one-phenylhydrazones with Antioxidant Properties: X-Ray Crystal and Spectroscopic Studies - Omoruyi G. Idemudia; Anthony I. Okoh; Alexander P. Sadimenko; Eric C. Hosten; Omobola O. Okoh (Journal of Chemistry)
Phenylhydrazine was reacted with synthesized acylpyrazolone derivatives 4-ethyl-5-methyl-2-phenyl-pyrazol-3-one and 4-propyl-5-methyl-2-phenyl-pyrazol-3-one, to obtain two new azomethine phenylhydrazones, a study in continuation of our probe into the effects of acyl group substitutions on the physicochemical and free radical scavenging properties of acylpyrazolone Schiff bases. The keto imine tautomers of 4-ethyl-5-methyl-2-phenyl-pyrazol-3-one-phenylhydrazone (Empp-Ph) and 4-propyl-5-methyl-2-phenyl-pyrazol-3-one-phenylhydrazone (Prmpp-Ph) according to single X-ray crystallography data which precipitated in good yield are reported. Furthermore they have been characterized by elemental analysis, FTIR, 13C and 1H NMR, and mass-spectroscopy techniques. Both phenylhydrazone Schiff bases crystallize in a triclinic crystal system, each with a space group of P-1 (number 2) having short intramolecular N3—H3…O1 hydrogen interaction between the first hydrazine hydrogen H3 and the pyrazolone oxygen O1. The antioxidant free radical scavenging activities of titled compounds against 2,2-diphenyl-1-picrylhydrazyl (DPPH) showed a positive response almost as good as that of vitamin c under the same conditions, with the propyl substituted 4-propyl-5-methyl-2-phenyl-pyrazol-3-one-phenylhydrazone (Prmpp-Ph) having a stronger activity (calculated IC50 value of 175.66 μg/ml).